The Use of AI Generative Feedback in Writing Theses for 8th-Semester Students English Education Study Program at the University of Bengkulu - Fradesta, Monica; Novita, Eka; Rosanda, Perti (UNIB Press, 2025)
Thesis writing in higher education poses a significant challenge for many students. With the rapid advancement of Artificial Intelligence (AI), students have begun using AI tools, particularly to obtain feedback during the writing process. This study investigates how AI-generated feedback is utilized in thesis writing and explores students’ perceptions of its effectiveness. Six eighth-semester students from the English Education Study Program at the University of Bengkulu were selected using criterion sampling. A qualitative phenomenological design was adopted, and data were collected through semi-structured interviews and documentation. Thematic analysis revealed that students used Chat GPT as their primary tool and engaged in three main activities: requesting, receiving, and responding to feedback. Participants reported that the feedback was generally helpful in improving the quality of their thesis writing, especially in terms of clarity, coherence, and self-revision. However, concerns regarding the relevance and accuracy of the feedback prompted them to verify it through self-evaluation, discussions with peers, or consultations with their supervisors. Despite its limitations, AI-generated feedback was perceived as a valuable support tool that enhanced students' autonomy and writing development. This suggests that while AI cannot fully replace human feedback, it can significantly contribute to the academic writing process by fostering independent learning and revision.